Variability of trace element concentrations in deposits of the Wolbrom and Otrębowskie Brzegi peatlands: a reflection of an anthropogenic impact: https://doi.org/10.26485/AGL/2018/10710 - Pawełczyk, Fatima; Okupny, Daniel; Michczyński, Adam (Acta Geographica Lodziensia, 2018)
A geochemical analysis was conducted on peat cores from two peatlands in Southern Poland that cover a time span from the Atlantic period (from 4900 BC in Wolbrom and from 4200 BC in Otrębowskie Brzegi) to modern times. The results were subjected to a statistical analysis using PAST software. The analysis was conducted taking into account previous botanical analyses, radiocarbon dating and lead-210 dating. The aim was to compare these two study sites in terms of their locations in different basins and anthropogenic activity. Elemental concentrations in the tested peat profiles were dependent on sediment type and their values range between very low (close to geochemical background values) and extremely high – especially in the case of heavy metals, like zinc and lead. The comparative analysis showed a synchronous record of local and regional changes of chemical composition in the two peatlands, which vary in terms of location, lithology and type of peat sediment.